RESPONSE OF ROOTSTOCKS AND VARIETIES ON GROWTH ARIETIES ON GROWTH ARIETIES ON GROWTH AND SURVIVAL PERCENTAGE IN EPICOTYL GRAFTING OF GE IN EPICOTYL GRAFTING OF MANGO ( MANGO (MANGIFERA INDICA L.) - PATEL, B. B.; TANK, R. V.; BHANDARI, A. J. (The Bioscan, 2016)
A field trial was conducted at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, Gujarat during 2012 to study the “Response of rootstocks and varieties on growth and survival percentage in epicotyl grafting of mango (Mangifera indica L).”. The results of experiment revealed that an early initiation of sprouting of mango graft was recorded with Rajapuri rootstock (8.33 days) and Sonpari as a variety (8.41days). Maximum number of graft established and sprouting percentage of graft at 1 month after grafting (MAG) was observed in Rajapuri as a rootstock (9.80) and Amrapali as a variety (10.41). Height of graft was maximum in Rajapuri as a rootstock (27.46, 29.22 and 36.42 cm) and Kesar as a variety (26.97, 28.87 and 35.79 cm) at 2, 4 and 6 MAG respectively. Maximum survival percentage of graft at 6 month after grafting was found in Deshi as rootstock (60.88%) and Sonpari as a variety (58.88%). Regarding interaction between rootstock and varieties, Deshi × Alphonso (71.10%), Rajapuri × Sonpari (71.10%) and Deshi × Amrapali (71.10%) were found superior for maximum survival of graft at 6 month after grafting